Manipulating Polarization via Optical Fiber Twisting for Optical Switch Applications - Surachart Kamoldilok; Jiratchayar Kadtajan; Athiwat Kanajirayupat; Keerayoot Srinuanjan (Journal of Physics Conference Series, 2025)
Abstract This research presents a method for controlling the polarization state of light in an optical fiber communication system. By twisting the optical fiber with three-paddle set polarization controllers where the birefringence occurs and polarization changes. Twisting the paddle in various conditions could be manipulated in the desired polarization state. The light is then launched into a Michaelson interferometer system, which includes a polarizing cube beamsplitter, where the output polarized state can be controlled and applied as an optical switch for an optical communication system.
Keywords: Semiconductor Lasers and Optical Devices; Optical Network Technologies; Advanced Optical Network Technologies